Defining the RBPome of primary T helper cells to elucidate higher-order Roquin-mediated mRNA regulation - Kai P. Hoefig (Nature Portfolio, 2021)
An extensive RNA binding protein atlas (RBPome) for primary T cells would be a useful resource. Here the authors use two different methods to characterise the mouse and human T cell RBPome and show regulation of Roquin-1/2 dependent and independent pathways.